Work Environemnt As A Moderating Variable Of The Influence Of Work Facility On Employee Performance - Septin Maisharah (Jurnal Teknologi dan Manajemen Industri Terapan, 2025)
This research is a quantitative research with an explanatory approach, namely an approach that makes previous research the main support for building, modifying, or adding to, and proving the hypotheses in this article. The data used in this research is primary data that the researcher obtained from one hundred lecturers and educational staff at STIKES Muhammadiyah Bojonegoro. The data obtained by the researcher was analyzed using the smart PLS 4.0 analysis tool. The result in this article shows that the Work Facilities variable can have a positive and significant influence on the Employee Performance variable because the P-Values ​​are positive and below the significance level of 0.05, namely 0.025. These results are in line with the research. These results indicate that Work Facilities can facilitate Employee Performance, make work results more qualified, and ultimately improve Employee Performance. In addition, the Work Environment variable can also moderate the influence of the Work Facilities variable on the Employee Performance variable because the same thing is that the P-Values ​​are positive and below the significance level of 0.05, namely 0.000, more significant than direct testing. Thus, a good work environment that supports employees in working, accompanied by Work Facilities, can significantly influence Employee Performance.